PEMANFAATAN PROFIL DAN RAPOR PENDIDIKAN MELALUI PlATFORM DIGITAL DALAM PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH SMP NEGERI 1 JEPON - Damayanti, Endang Sri; Poyo; Harum K., Sri Maya; Nurkolis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
New developments in information technology have paved the way for innovative possibilities in education management, particularly when it comes to overseeing and enhancing education quality at the Elementary School (SD) and Middle School (SMP/SMA) levels. In Indonesia, the Ministry of Education, Culture, Research, and Technology has initiated the Education Report Platform, which features detailed data for each educational institution. This article discusses the concepts of education profile, education report, and education report platform, and how all three can be utilized in the planning and decision-making process to improve the quality of education at the elementary and secondary levels.